Методы и алгоритмы расчета тепловых сетей - Хасилев В. Я. Виктор Яковлевич; Меренков А. П. Анатолий Петрович; Каганович Б. М. Борис Моисеевич; Светлов К. С. Константин Сергеевич; Такайшвили М. К. Михаил Константинович (Москва, Энергия, 1978)
Авт. указаны на обороте тит.